Revolutionizing speaking skills improvement: AI’s role in personalized language learning - Nhan, Lam Ky; Hoa, Nguyen Thi My; Quang, Luong Vo Nhat (International Journal of Innovative Research and Scientific Studies, 2025)
Artificial Intelligence (AI) integration into language learning and teaching has been an area of educational research interest with a focus on developing speaking skills. With the promising capability of AI-powered tools to address Foreign Language Anxiety (FLA), facilitate self-regulated learning, and provide customized instruction, there is a growing but limited empirical investigation into the effects of these technologies on real-world language learning. It will explore the potential of AI-assisted Language Tools in tackling these challenges and improving speaking proficiency. The study employed a mixed methods approach to capture qualitative and quantitative data from language learners who were using AI-powered speaking platforms. Results show that AI tools help alleviate foreign language anxiety (FLA) by offering an environment that is low-stakes and free of judgment, allowing learners to speak readily, fostering a sense of more confidence and willingness to practice speaking. Moreover, the research underscores the significance of AI in promoting self-regulated learning by providing personalized constructive feedback and adaptive learning environments, thus enabling students to self-monitor their advancement and develop their speaking competencies independently. AI systems can tailor instruction to the needs of the individual learner, allowing for more inclusive and targeted language learning experiences, the research also indicates. This study puts a spotlight on how AI technologies need to be integrated into language curricula, especially for learners who face language barriers or psychological barriers such as anxiety in their journey to learning a new language.